If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + x + z = 1 Reorder the terms: x + 2y + z = 1 Solving x + 2y + z = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y + z = 1 + -2y Combine like terms: 2y + -2y = 0 x + 0 + z = 1 + -2y x + z = 1 + -2y Add '-1z' to each side of the equation. x + z + -1z = 1 + -2y + -1z Combine like terms: z + -1z = 0 x + 0 = 1 + -2y + -1z x = 1 + -2y + -1z Simplifying x = 1 + -2y + -1z
| 3y(y-2)+4(y-2)= | | y+4=5mx | | -3(9n+6)=-28+7n | | 2w+3=4w+3 | | 24+6+4x=3.167 | | 3(-4y+37)+2y=31 | | f(x)+1=81 | | -10x-42=33-7x | | -50-7x=78+x | | -4x-147=105+10x | | 3x-28=-x+60 | | 12.4y+140=60y-20 | | 3(4y+1)-2=49 | | 14(13)+55=11(13)+94 | | 7x-71=x+79 | | 3x-71=145+11x | | 3+7=55 | | -11x-106=-x+54 | | 6x-105=-12x+165 | | y^2(x+5)+5y(x+5)-14(x+5)=0 | | 6x-19=3x+10 | | -6x-50=18-10x | | -5x-88=38+9x | | 3y+5-1y= | | -44-3x=5x+60 | | 2x-63=49-5x | | 0.75X+X=63 | | 0.75(48-16x)=4(4+2x) | | 8d-12=-4 | | 4x-95=-6x+65 | | 18-2.3d=1.9 | | 5x-67=87-6x |